Contribution of Premature Baby (the Low Birth Weigh) towards Postpartum Depressed Mother - M. Maryatun; I. Indarwati; W. Widaryati (Gaster, 2022)
Postpartum depression is a common phenomenon and has the complexities which bringing on adverse consequence for mother, baby, and family. The reference of this research provides an overview of the various risk factors for postpartum depression. This research is aimed to identify various risk factors such as level of depression, postpartum type, husband’s support, baby weight, parity and number of children. Those factors can be the cause of postpartum. Women with postpartum depression who have the baby in low weight can be identified as the strongly predictor factor of postpartum depression cause. The method applied in this research is an observational research with cross sectional design which involving 75 postpartum mothers who having live babies. Data analysis is conducted by chi-square that presents the correlation of baby in low weight and the incidence of depression indicated on p value less than 0,05. Data are collected at once time. Result shows that there is a correlation of childbirth type, social support, baby weight, and parity toward the incidence of postpartum depression. This research provides a crucial reference about mother with postpartum depression that can be caused by the birth of low baby weigh. For further researchers, it can be an insight for analysis as the effort of baby and mother care in case to prevent the postpartum depression.